Traumatic Dislodgement of Tibial Polyethylene Insert after a High-Flex Posterior-Stabilized Total Knee Replacement - Juan Felix Astoul Bonorino; Pablo Ariel Isidoro Slullitel; Gonzalo Rodrigo Kido; Santiago Bongiovanni; Renato Vestri; Lisandro Carbó (Case Reports in Orthopedics)
Many pathologic entities can produce a painful total knee replacement (TKR) that may lead to potential prosthetic failure. Polyethylene insert dissociation from the tibial baseplate has been described most frequently after mobile-bearing and cruciate-retaining TKRs. However, only 3 tibial insert dislocations in primary fixed-bearing High-Flex posterior-stabilized TKRs have been reported. We present a new case of tibial insert dislocation in a High-Flex model that shares similarities and differences with the cases reported, facilitating the analysis of the potential causes, which still remain undefined.